Levosimendan in Decompensated Heart Failure with Reduced Ejection Fraction in Older Adults: A Systematic Review of Safety and Efficacy. - Zavaleta Monestel, Esteban (2025)
Background/objectives: Heart failure with reduced ejection fraction (HFrEF) is a leading cause of hospitalization and functional decline in older adults, accounting for over 80% of all heart failure cases. Given the narrow therapeutic window of currently available inotropes and the vulnerability of this population, levosimendan has been proposed as a potential alternative. This systematic review aimed to evaluate the clinical efficacy and safety of levosimendan in older adults with decompensated HFrEF. Methods: A systematic search of PubMed, Embase, Scopus, and the Cochrane Library was conducted between January and May 2025, following PRISMA 2020 guidelines. The review was registered in PROSPERO (CRD420251032329). Of 379 articles initially identified, 8 studies (randomized, observational, and single-arm designs) enrolling patients aged ≥65 years with decompensated HFrEF met the inclusion criteria. Study quality was assessed using the Cochrane RoB-2 tool and JBI Critical Appraisal Checklists. No meta-analysis was performed due to heterogeneity in study designs, populations, and interventions. Results: A total of 2838 patients were analyzed. Levosimendan was associated with short-term improvements in hemodynamic parameters, including an increase in cardiac index (from 1.65 to 2.37 L/min/m2) and a reduction in pulmonary capillary wedge pressure (from 31 to 16 mmHg) within 24-72 h (p < 0.002). However, no statistically significant differences were observed in 30-, 90-, or 180-day mortality (p > 0.05), and findings on rehospitalization were inconsistent. Reported adverse events included hypotension (36-57%) and atrial arrhythmias (9-50%), with low treatment discontinuation rates (5-8%). Conclusions: Levosimendan may improve short-term hemodynamic parameters in older adults with decompensated HFrEF, but the available evidence is limited and heterogeneous. Its effects on mortality and rehospitalization remain inconclusive. Clinical use should be individualized and closely monitored, particularly in frail patients.